(3GJLGgGJ GdLeghQ fMh eYGdLI GdOQGeG GdJdaRjhfjI deTcdI GdYfhSI aj GdeLJeY GdeUQj (B/ s - (3EjfGS eMeO Ydi GdTjN s; (3HQcGJ YHOGdYRjR (B: s ((3GdbGgQI (B: s (3EjfGS eMeO Ydi GdTjN (B: s, 2016)
(3SYJ GdOQGSI Edi QUO hJMdjd GJLGgGJ GdLeghQ GdeTGgO HGdaYd ddOQGeG GdJdjaRjhfjI ShGA cGfJ CadGe Ch eSdSdGJ eUQjI JfGhdJ Ch fGbTJ eTcdI GdYfhSI hJCNQ GdRhGL ai GdeLJeY GdeUQj (B: (3hQUO hJMdjd eYOd GdJYQV hOhGaY GdeTGgOI deKd gPg GdOQGeG(B: (3hJMdjd UhQI GdaJGg GdZjQ eJRhLI ef UaGJ EjLGHjI hSdHjI hCHQR eNGhagG ceG JYQVgG GdOQGeG GdJdjaRjhfjI ef hLgI fXQ GdLeghQ hGdhbha Ydi JbjeGJ GdLeghQ ddOQGeG GdJdjaRjhfjI GdJi JJfGhd eTcdI GdYfhSI hebJQMGJge dJaYjd OhQ GdOQGeG aj eYGdLI GdbVGjG GdELJeGYjI (B: (3hJe Pdc ef NdGd GSJNOGe UMjaI GdGSJHjGf deYQaI GJLGgGJ GdLeghQ(B: (3Je JhRjYgG Ydi YjfI YThGFjI bhGegG (B450 (3eaQOI ef GdLeghQ GdYGe GdeTGgO ddOQGeG GdJdaRjhfjI GdJi JJfGhd eTcdI GdYfhSI (B: (3hJe GSJHYGO (B50 (3eaQOI dG jTGgOhf GdOQGeG GdJdaRjhfjI (B: (3ceG Je JhRjYge aj eMGaXGJ (B((3GdbGgQI(B: (3GdefhajI(B: (3GdefjG(B) (3ef Sf (B25 (3SfI aCcKQ(B: (3hJhUdJ GdOQGSI Edi Cf GdOQGeG GdJdjaRjhfjI GdJj JfGhdJ eTcdI GdYfhSI SGgeJ Edi MpqO eG aj GdJYQja HGdeTcdI aj GdeLJeY GdeUQj HfSHI (B42.4%: (3HjfeG SGgeJ GdOQGeG HGdaYd aj GdJYQja HGdeTcdI HfSHI (B26.7% : (3Ydi Mjf de JSge GdOQGeG aj GdJYQja HGdeTcdI HfSHI (B30.9%: (3ceG CcOJ GdOQGSI Ydi GdaQV GdbGFd HhLhO aQhb PGJ OdGdI GMUGFjI Hjf GdeHMhKjf YjfI GdOQGSI ai GJLGgGJge fMh eYGdLI GdJdjaRjhf deTcdI GdYfhSI HMSH NUGFUge GdOjehLQGajI (B((3LRFjkG(B) : (3hNQLJ GdOQGSI HJhUjGJ efgG VQhQI GgJeGe GdOQGeG GdJdjaRjhfjI HhVY Mdhd deTcdI GdYfhSI hYOe GdEcJaGA HYQV GdeTcdI abW (B: (3hVQhQI hLhO MdbI hUd Hjf GdbGFe Ydi GdOQGSI hGdbGFejf HGdYed Ydi cJGHI GdSjfGQjh ddOQGeG GdJdjaRjhfjI dJhLjg GdOQGeG HWQjbI UMjMI hefgLjI dMd GdbVGjG GdELJeGYjI ai GdeLJeY HWQjbI UMjMI (B. s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdGYdGe (B- (3bSe GdEPGYI hGdJdjaRjhfs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GJLGgGJ GdLeghQ s; (3GdOQGeG GdJdaRjhfjIs; (3eTcdI GdYfhSIs